2016
DOI: 10.1002/joc.4724
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly based analysis of extreme heat waves in Eastern China during 1981-2013

Abstract: This study shows applications of an anomaly based analysis method to describe extreme summer heat waves in Eastern China during 1981-2013 using two reanalysis products. These events are defined in an area of a spatial size larger than 300 × 500 km (0.15 × 10 6 km 2 ) when its daily maximum surface air temperature (DMSAT) exceeds 35 ∘ C, and the DMSAT anomaly is no less than 5 ∘ C for at least five consecutive days. Results show that by extracting the transient anomalies, the anomaly based method can substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 22 publications
9
49
0
Order By: Relevance
“…Similar results were obtained by Chen et al [9], who investigated atmospheric circulation during the selected HWs in China between 1981 and 2013. They proved that a strong signal of positive geopotential height anomalies in the upper troposphere is responsible for the surface heat wave and indicated the possibility of predicting the occurrence of HWs on the basis of observations of disturbances in the higher layers of the troposphere.…”
Section: Discussion and Summarysupporting
confidence: 88%
See 2 more Smart Citations
“…Similar results were obtained by Chen et al [9], who investigated atmospheric circulation during the selected HWs in China between 1981 and 2013. They proved that a strong signal of positive geopotential height anomalies in the upper troposphere is responsible for the surface heat wave and indicated the possibility of predicting the occurrence of HWs on the basis of observations of disturbances in the higher layers of the troposphere.…”
Section: Discussion and Summarysupporting
confidence: 88%
“…As for the duration, the WMO advice is that a heat wave should be considered a hot period "persisting [for] at least two consecutive days" [25]. Different duration thresholds are chosen, from ≥2 consecutive days in Canada [29], ≥3 days in France [27], Greece [30], Hungary [31], ≥5 days in Ukraine [7], China [9], Australia [32] up to ≥6 consecutive days in Bulgaria [33]. In human biometeorology defining heat waves is usually more complex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though there is no simple relationship between air temperature and morbidity and mortality, high correlation between certain extreme temperatures and mortality has been demonstrated worldwide (Knowlton et al, 2009;Barnett et al, 2012). HWs cause more deaths all over the world than any other natural hazards (Unkaševic and Tošic, 2009;D'Ippoliti et al, 2010;Peterson et al, 2013;Shaposhnikov et al, 2014;Liu et al, 2015;Nairn and Fawcett, 2015;Kim et al, 2016;Chen et al, 2017). Some previous studies showed an increase in the number of deaths during HWs: between 3.0 and 7.8% in the United States of America (Medina-Ramón and Schwartz, 2007;Anderson and Bell, 2009;Peng et al, 2011), 21.8% in the Mediterranean areas (D'Ippoliti et al, 2010), 16.5% in Spain , 5% in China (Ma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The common feature observed in all global heat wave cases is the presence of a high-pressure synoptic system (anticyclone) (Black et al, 2004;Dole et al, 2011;Barriopedro et al, 2011;Parker et al, 2014;Murari et al, 2015;Wang et al, 2017). In addition, the heat waves are in general associated with pressure, temperature, geopotential height, and wind anomalies (Deshpande and Ernestraj, 2007;Cerne et al, 2007;Murari et al, 2015;Lee and Lee, 2016;Qian et al, 2016;Rohini et al, 2016;Chen et al, 2017). Also, the occurrence and longevity of heat wave can be governed by specific synoptic conditions.…”
Section: The Role Of Atmospheric Circulationmentioning
confidence: 99%